Explore the Association of Anger with Academic Year Among Nursing Students at Private Nursing Institute Karachi Pakistan : Explore the Association of Anger with Academic Year Among Nursing Students - Bibi, Afsha; Khaliq, Fazal; Ishaq, Muhammad; Ahmad, Hammad; Rasool, Hafiz Asim; Mahmood, Saqib (Pakistan BioMedical Journal, 2024)
Anger among nursing students can stem from various sources, considering the demanding nature of their education and future profession. Objective: To explore the association of anger with academic year among nursing students at a private nursing institute in Karachi, Pakistan. Methods: This cross-sectional study was conducted at Horizon School of Nursing and Health Sciences: 128 nursing students were recruited through convenient sampling. Nursing students enrolled in various academic years were included. Results: The study findings revealed that the participants are predominantly male, making up 85.6% of the sample, while females represent 14.4%. Moreover, the findings revealed that the mean anger score is calculated at 28.8366, indicating the average level of anger reported by nursing students. The findings also include p-values, highlighting significant differences in academic years (p = 0.016) but not in gender (p = 0.156) or age groups (p = 0.440). The study found average anger levels among nursing students (28.8366). Academic years showed significant differences in anger (p = 0.016), while gender (p = 0.156) and age (p = 0.440) did not. Conclusions: Tailored support for specific program stages could enhance student well-being.